INVESTIGATING THE EFFECT OF REFLEXOLOGY IN INTENSITY OF PAIN AND ANXIETY AMONG PATIENTS SUFFERING FROM METASTATIC CANCER IN ADULTS' HEMATOLOGY WARD - Jahani, Simin; Salari, Fatemeh; Elahi, Nasrin; Cheraghian, Bahman (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Findings suggest dissatisfaction of half of the cancer patients regarding pain and anxiety management. This study aimed to determine the effect of reflexology on the intensity of pain and anxiety among patients with metastatic cancer hospitalized inadulthematology ward. Â Â Methods: In this study, the samples were selected from adult hematology ward in Baghaei 2 hospital in Ahwaz, Iran, according to the inclusion criteria. They were then assigned into treatment and control groups. In the treatment group, reflexology protocol was performed following manual reflexology method by Fr Josef Eugster based on Ingham method on the patient's bed. In the control group, sole touching was used as the placebo. Reflexology was performed for three days, 30 min per day. Spielberger questionnaire were provided to the samples and completed in the first and third days, and Spielberger questionnaire was provided to the samples and completed. The data obtained from this study were then analyzed by SPSS 20. Results: The two groups did not show a significant difference in terms of demographic characteristics (p>0.05). Based on the obtained results, it was found that in the test group, there was a significant difference between the mean intensity of pain before and after the treatment across all 3 days as well as the mean anxiety of the 1st and 3rd days (p<0.05). However, in the control group, there was no significant difference in terms of mean pain intensity before and after the treatment across 3 days (p>0.05). No significant difference was observed between the mean anxiety of the 1st and 3rd days either (p>0.05). Conclusion: Considering the findings of this research, it can be concluded that reflexology has a positive effect on mitigating the intensity of pain and anxiety in metastatic cancer patients. Therefore, it is recommended that nurses employed in cancer centers benefit from the findings of this research to further help patients with cancer. It is also suggested that further research be conducted on the effect of reflexology on the pain and anxiety of other patients.